2022
DOI: 10.1002/mdc3.13520
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Non‐Motor Fluctuations Using the Movement Disorder Society Non‐Motor Rating Scale

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Prevalence of non-motor fluctuations were found in 26.1% of the participants, and increased with severity of PD. These results were slightly lower overall than the frequency of NMF in the MDS-NMS study of 9.1% for <2 years of disease duration, 54.3% for 2–5 years, 63.6% for 5–10 years, and 71.0% for ≥10 years, with an average of 49.2% ( 22 ). It is known that factors such as older age, disease duration, reduced activity of daily living, severity of motor symptoms, and long off-time reduce the QOL score of PwPD ( 23 ).…”
Section: Discussionmentioning
confidence: 62%
“…Prevalence of non-motor fluctuations were found in 26.1% of the participants, and increased with severity of PD. These results were slightly lower overall than the frequency of NMF in the MDS-NMS study of 9.1% for <2 years of disease duration, 54.3% for 2–5 years, 63.6% for 5–10 years, and 71.0% for ≥10 years, with an average of 49.2% ( 22 ). It is known that factors such as older age, disease duration, reduced activity of daily living, severity of motor symptoms, and long off-time reduce the QOL score of PwPD ( 23 ).…”
Section: Discussionmentioning
confidence: 62%
“…According to a recent study, prevalence of NMF, evaluated by the means of the MDS-NMS rating scale (Chaudhuri et al 2020 ), was low (9.1%) in the very early stage (< 2 years), showing a rapid increase between 2 and 5 years (54%) and a substantial plateau thereafter (van Wamelen et al 2022 ). In our cohort prevalence of NMF (71.9%) was high and quite stable across the disease duration.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified that up to 23.1% of patients with PD experience cognitive NMF (assessed using the MDS Non-Motor Rating Scale) [ 30 ]. Its prevalence increases as the disease progresses, with the highest prevalence in patients with a disease duration > 10 years [ 32 ]. Occasionally, individuals may experience ‘on’ period bradyphrenia and difficulties in memory retrieval, which could also be attributed to the cognitive side effects of L-dopa, as discussed below [ 33 ].…”
Section: Cognitive Disorders In Pdmentioning
confidence: 99%
“…Cognitive NMF can manifest with an acute onset inattention and fluctuating arousal, typically occurring when the effect of L-dopa disappears. Fluctuations tend to increase over the course of the disease, implying that patients with a higher NMF burden will probably have more severe PD-CI and more predisposing factors for delirium [ 32 ]. Additionally, severe motor “off” states or NMS such as unnoticed orthostatic hypotension may also mimic symptoms of delirium.…”
Section: Diagnostic and Therapeutic Challenges And Caveatsmentioning
confidence: 99%